Interaction between the human nuclear cap-binding protein complex and hnRNP F. - Gamberi, C (1997)
hnRNP F was identified in a screen for proteins that interact with human CBP80 and CBP20, the components of the nuclear cap-binding complex (CBC). In vitro interaction studies showed that hnRNP F can bind to both CBP20 and CBP80 individually. hnRNP F and CBC bind independently to RNA, but hnRNP F binds preferentially to CBC-RNA complexes rather than to naked RNA. The hnRNP H protein, which is 78% identical to hnRNP F and also interacts with both CBP80 and CBP20 in vitro, does not discriminate between naked RNA and CBC-RNA complexes, showing that this effect is specific. Depletion of hnRNP F from HeLa cell nuclear extract decreases the efficiency of pre-mRNA splicing, a defect which can be partially compensated by addition of recombinant hnRNP F. Thus, hnRNP F is required for efficient pre-mRNA splicing in vitro and may participate in the effect of CBC on pre-mRNA splicing.